POTENTIAL DRUG TARGETS FOR ALOIN AND MICRODONTIN: AN IN-SILICO ANALYSIS - Ravi, Lokesh; Ragunathan, Adhithya (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The aim of this study was to study the interactions of Aloin and microdontin with antimalarial drug targets. Methods: The ADMET properties of Aloin and microdontin were analyzed using LigandScout and Osiris Molecular Property Predictor tools. The protein-ligand docking was performed in AutoDock software. AutoDock result was analyzed using PyMol and LigPlot+ software. Results: ADMET analysis suggests no major side effects for both Aloin and microdontin. Docking results show that Aloin had the highest significance with Plasmodium falciparum calcium-dependent protein kinase (PfCDPK2) with a free binding energy of –8.01 Kcal/Mol, Ki value of 1.35 µM and 6 hydrogen bonds. Microdontin had the highest significance toward Glutaredoxin-1 with –8.04 Kcal/Mol, Ki value of 1.28 µM and 3 hydrogen bonds. Conclusion: Based on the observed results for the studied drug targets, the proposed mechanism of action of Aloin is suggestively concluded as PfCDPK2 and for microdontin as glutaredoxin-1. Keywords: Anti-malaria, Aloin, Microdontin, Autodock, Ligandscout.